AN ANALYSIS OF ENGLISH FOREIGN LANGUAGE (EFL) STUDENTS’ ANXIETY IN SPEAKING CLASS - Monika Herawaty; Desi Sri Astuti; Elly Syahadati (XXXX-XXXX, 2021)
This research aimed find out the most common cause of English Foreign Language (EFL) students’ anxiety in speaking class to the Third Semester Students of English Education Study Program of IKIP PGRI Pontianak. The subject of this research was only one class, the number of subject was 31 students from B Morning class. This research was a descriptive research. The data collected from the questionnaire and interview. The data which have been collected are analyzed by using google form as a tool to collect the data.  The findings showed the percentages of English Foreign Language (EFL) students’ anxiety in cognitive, behavioural, and physiological factors. The mean score of English Foreign Language (EFL) students’ anxiety in cognitive factor was 74.2% Then, the mean score in behavioural factor was 74%. And then the mean score in physiological factor was 72%. The students in speaking class they are lack of preparation, fear of making mistakes, afraid of the classmates that they could not do their best in speaking class. With these findings, therefore the researcher concluded that the most common cause of English Foreign Language (EFL) students’ anxiety in speaking class was cognitive factors. Keyword: English Foreign Language (EFL) students’ anxiety, speaking anxiety, descriptive research.